1996
DOI: 10.1104/pp.112.4.1687
|View full text |Cite
|
Sign up to set email alerts
|

An Ethylene-Mediated Increase in Sensitivity to Auxin Induces Adventitious Root Formation in Flooded Rumex palustris Sm

Abstract: The hormonal regulation of adventitious root formation induced by flooding of the root system was investigated in the wetland species Rumex palusfris Sm. Adventitious root development at the base of the shoot is an important adaptation to flooded conditions and takes place soon afler the onset of flooding. Decreases in either endogenous auxin or ethylene concentrations induced by application of inhibitors of either auxin transport or ethylene biosynthesis reduced the number of adventitious roots formed by floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
142
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(152 citation statements)
references
References 25 publications
6
142
0
4
Order By: Relevance
“…While no change in the endogenous free auxin concentration was detected upon flooding, blocking polar auxin transport with N-1-naphtylphtalamic acid (NPA) decreased the number of ARs after flooding (Visser et al, 1996c). Reconciling these findings, it was found that accumulation of ethylene leads to AR emergence by increasing the sensitivity to auxin in the rooting zone (Visser et al, 1996c).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…While no change in the endogenous free auxin concentration was detected upon flooding, blocking polar auxin transport with N-1-naphtylphtalamic acid (NPA) decreased the number of ARs after flooding (Visser et al, 1996c). Reconciling these findings, it was found that accumulation of ethylene leads to AR emergence by increasing the sensitivity to auxin in the rooting zone (Visser et al, 1996c).…”
mentioning
confidence: 77%
“…In R. palustris, ethylene accumulation was observed in roots following 24 h of submergence, and inhibition of ethylene production decreased the number of ARs induced by flooding (Visser et al, 1996b). While no change in the endogenous free auxin concentration was detected upon flooding, blocking polar auxin transport with N-1-naphtylphtalamic acid (NPA) decreased the number of ARs after flooding (Visser et al, 1996c). Reconciling these findings, it was found that accumulation of ethylene leads to AR emergence by increasing the sensitivity to auxin in the rooting zone (Visser et al, 1996c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ramets of each species were taken from the plants in the glasshouse and placed in rafts floating in containers of well aerated nutrient solution as described in Visser et al (1996c). After the development of a new root system, five to eight plants per species were transferred to a stagnant, oxygen-deficient nutrient solution containing 0n1% agar (Visser et al, 1996c).…”
Section: Hydroponic Experimentsmentioning
confidence: 99%
“…It is well established that exogenous application of auxin accelerates the rates of rooting, increases final rooting percentage and the number of produced roots in leafy cuttings (Leakey, 1990;Larson, 1992;De Klerk et al, 1999), which could be attributed to the translocation of carbohydrates and other nutrients to the rooting zone (Middleton et al, 1980;Leakey et al, 1982). However, exogenous application of auxin may be promotive, ineffective or even inhibitory for the rooting of cuttings, depending on the endogenous level of growth-regulating substances (Haissig, 1979) or the tissue sensitivity (Visser et al, 1996). Relatively high concentrations of auxins have been reported to be inhibitory to rooting, indicating that in many species, optimal concentrations for rooting have to be defined (Leakey et al, 1982).…”
Section: Introductionmentioning
confidence: 99%